NON-STANDARD FORMS OF ORGANIZING RUSSIAN LANGUAGE TEACHING IN NATIONAL GROUPS OF MILITARY UNIVERSITIES - Akhmedova Nilufar Yakhiyaevna (Galaxy International Interdisciplinary Research Journal, 2023)
Our country is a comprehensively developed, knowledgeable, dedicated to serving its people, as well as its Motherland, within the framework of the implementation of the accepted concepts of educating youth in a military-patriotic spirit and increasing the effectiveness of spiritual and educational activities in the education system in military higher educational institutions, a large-scale work on educating cadets. We think about the importance of working in groups to educate fully mature, physically healthy and spiritually mature young people with high intellectual potential, modern thinking and worldview, who are ready to selflessly defend the interests and sovereignty of our country.